Obdelovanje tal in protierozijska zaščita na vodovarstvenih območjih - Stajnko, Denis (University of Maribor Press, 2017)
Soil Tillage and Anti-Erosion Protection at Water Protection Zones. The monograph was prepared to educate agricultural advisors and farmers on the modern ways of soil tillage at water protection zones (WPZ), comprising of wellhead protection area, intake protection zone, significant groundwater recharge area and highly vulnerable area. It was prepared for the project SI-MUR-AT, an EU Cooperation Program INTERREG Slovenia-Austria 2014 – 2020. WPZ represents source water (including water from lakes, rivers and underground aquifers) protection from overuse and contamination. Since WPZ is usually the part of agricultural landscape, the water quality might be affected by the improper agricultural practices. In the first part the most important regulation on the way of conventional farming, especially soil tillage, fertilization is described as suggested by local and state legislative. The major part is contributed to the conservation agriculture (CA), whereby the conservation tillage (CT) represents the only acceptable way of preparing the soil for sowing. Beside CT systems no or minimum mechanical soil disturbance, organic mulch soil cover, and crop species diversification is presented in this monograph.